Foreword - Angelo, AH; McLay, Geoff; Marten, Bevan (Victoria University of Wellington Law Review, 2015)
This article is the foreword to a special issue of this Victoria University of Wellington Law Review celebrating Professor Bill Atkin's 40th year at the Victoria University of Wellington Faculty of Law. The issue contains personal tributes to Professor Atkin, as well as articles focused on Professor Atkin's areas of focus including family law, torts, accident compensation, medico-legal issues, and welfare law.